PEMANFAATAN RISET BIODIVERSITAS DALAM PENDIDIKAN BIOLOGI DAN PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN DI ERA TEKNOLOGI 4.0 - Slamet Suyanto (Prosiding Seminar Nasional Biotik, 2019)
Idonesia is one of the top ten countries in the world that has mega-biodiversity. The government claims an exclusive economic zone of Indonesia is totally about 7.9 million square kilometers and ranks the second on the tropical rain forest (after Brazil) which is inhabited by more than two third species of the world.  The mega-biodiversity is reinforced by the unique edaphic, climatic, and aquatic conditions. However, the diversity is recently endangered by several factors, such as fires, illegal logging, farming, mining, fishing, and pollution.  The rapid human population growth also has negative impacts on the biodiversity. To maintain the biodiversity of species and their environment, biology education is required to develop characters of young generations with great affection on the environment and living things who are committed to preserving and conserving biodiversity. Computer and information technology is also required to promote their learning.